SIMULASI GERAK DAN ANALISIS KESTABILAN KOPLING INERSIA WAHANA DIRGANTARA DENGAN BENTUK BADAN RAMPING - Hari Muhammad; Hilman Samputra; Yazdi I. Jenie; Javensius Sembiring (National Institute of Aeronautics and Space - LAPAN, 2011)
Inertia coupling is a motion phenomenon of a high-speed airplane having slender body and low aspect ratio. This inertia coupling happens when the aircraft performs a roll manoeuvre motion with a high roll rate. This paper will discuss the derivation of inertia coupling equations of motion, modelling equations of motion in the Matlab/Simulink software, simulating the dynamics motion, and analyzing the stability of the inertia coupling. Numerical simulation and stability analysis of the inertia coupling for a fighter aircraft will be presented in this paper. Keywords:Inertia coupling, Stability analysis, Flight simulation, Slender body